Comparative transcriptomic analysis of gill reveals genes belonging to mTORC1 signaling pathway associated with the resistance trait of shrimp to VPAHPND - Liu, Yuan; Yu, Yang; Li, Shihao; Sun, Mingzhe; Li, Fuhua (Frontiers in Immunology, 2023)
Selective breeding for acute hepatopancreatic necrosis disease (AHPND) resistant shrimp is an effective way to deal with heavy losses to shrimp aquaculture caused by AHPND. However, knowledge about the molecular mechanism of susceptibility or resistance to AHPND is very limited. We herein performed a comparative transcriptomic analysis of gill tissue between AHPND susceptible and resistant families of the white Pacific shrimp Litopenaeus vannamei during Vibrio parahaemolyticus (VPAHPND) infection. A total of 5,013 genes that were differentially expressed between the two families at 0 and 6 h post-infection, and 1,124 DEGs were shared for both two time points. Both GO and KEGG analyses in each or two time point’s comparisons showed DEGs involved in endocytosis, protein synthesis and cell inflammation were significantly enriched. Several immune DEGs including PRRs, antioxidants and AMPs were also identified. The susceptible shrimp showed enhanced endocytosis, higher aminoacyl-tRNA ligase activity and occurrence of inflammatory response, while the resistant shrimp had much more strong ability in ribosome biogenesis, antioxidant activity and pathogen recognition and clearance. These genes and processes were mostly associated with mTORC1 signaling pathway, which could reflect differences in cell growth, metabolism and immune response between the two families. Our findings indicate a close link between mTORC1 signaling-related genes and Vibrio-resistance phenotype of shrimp, and provide new clues for further research on resistance strategy of shrimp to AHPND.